Automated Hydroponic System for Indoor Plant Growth in Urban Area - Cong, Mek Zi; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2020)
The need for an indoor hydroponic farming system as an alternative source for own food consumption spikes interest among urban citizens. Despite their hectic lifestyle, they generally do not have time to build their own farm and need an automated system to minimize operations in farming. In this paper, an automated indoor hydroponic is developed to allow urban citizens to grow the plant indoor. The system is developed with NodeMCU Esp8266 to control relevant parameters by using an actuator and monitor the parameters via a mobile application. The system has been tested to grow Pak Choy in an indoor environment and continuous monitoring through mobile apps demonstrates that a more stable plant growth parameters trend can be achieved as compared to the outdoor environment. The automated hydroponic system provides an efficient way to grow a plant in the indoor environment by resulting in a faster growth rate and bigger leaf size.